Modifiable vascular risk factors, white matter disease and cognition in early Parkinson's disease. (28th October 2018) - Chahine, L. M.; Dos Santos, C.; Fullard, M.; Scordia, C.; Weintraub, D.; Erus, G.; Rosenthal, L.; Davatzikos, C.; McMillan, C. T.
Abstract : Background and purpose: Dementia in Parkinson's disease (PD) is common and disabling. Identification of modifiable risk factors for it is essential. Vascular risk factors (VRFs) may be associated with cognitive decline in early PD. Biomarkers that serve as surrogates of the long‐term effect of VRFs on PD are needed. To that end, we aimed to quantitate white matter hyperintensities (WMH) in early PD, measure associations with VRFs and examine relationships between WMH and longitudinal cognition. Methods: Participants in the Parkinson's Progression Markers Initiative study (141 patients with PD, 63 healthy controls) with adequate baseline structural brain magnetic resonance imaging data were included. Hypertension and diabetes history, and body mass index were combined to create a vascular risk score. WMH were quantitated via automated methods. Cognition was assessed annually with a comprehensive test battery. Results: In the PD group, vascular risk score was associated with WMH for total brain (β = 0.210; P  = 0.021), total white matter (β = 0.214; P  = 0.013), frontal (β = 0.220; P  = 0.002) and temporal (β = 0.212; P  = 0.002) regions. Annual rate of change in global cognition was greater in those with higher vascular risk score (β = −0.040; P  = 0.007) and greater WMH (β = −0.029; P  = 0.049). Higher temporal WMH burden was associated with great decline over time in verbal memory (β = −0.034; P  = 0.031). Conclusions: In early PD, modifiable VRFs are associated with WMH on brain magnetic resonance imaging. Temporal WMH burden predicts decline in verbal memory. WMH may serve as a surrogate marker for the effect of VRFs on cognitive abilities in PD.